Metagaming: cognition in gaming environments and systems - Lickteig, Seth Jordan (Kansas State University, 2020)
The primary purpose of this focus group study was to explore how learning occurs during iterative experiences within a singular games-based environment. Using constructivist learning theories as a foundation, this study sought to identify how those processes were used in games-based settings. This qualitative study included eight undergraduate participants primarily in education-based fields. Over the span of six weeks, participants learned the game of Magic the Gathering, its rules, mechanics, and systems. Research questions sought to identify what was learned, how it was learned, and why the learning was effective. Four total focus group interviews were conducted, which were recorded and subsequently transcribed. Initial coding, axial coding, and analytic memoing were employed during data analysis, resulting in a tiered approach that refined data into patterns and then further into potential themes. Additionally, participants kept an on-going reflective journal in which they recorded their experiences with the game outside of the focus group meetings. Findings suggest participants engaged with the game system in a variety of ways, demonstrating high-level skill incorporation and practice. With repeated play, participants naturally began to inquire into the deeper workings of the game. This resulted in participant learning which included both mechanical and social forms of metagaming. Mechanical metagaming reflects the learning which occurs when engaging directly with the game systems, mechanics, and processes. Players analyze and synthesize complex systems in making determinations that inform future gameplay. Social metagaming signifies the understanding of peers during gaming environments. When playing against familiar opponents, participants made evaluations dependent on the personality and strategies of that particular opponent. Participant learning took place via an inquiry-based approach which allowed individuals to approach the game from their own perspectives and for personalized purposes. Learning was effective because it took place in a social environment, was reinforced by emotional responses to gameplay, and was highly personalized for each participant. Implications from this study suggest a games-based approach to learning can be organized and structured to provide students with the opportunity to form a deep understanding of higher skills through direct engagement with a game. The study theorizes the use of a games-based inquiry approach to classroom pedagogy, where a game serves as the primary object of study. Instead of games serving as a single-use form of additional media for disciplinary content delivery, students explore the game itself in repeated playthroughs. This arrangement allows for direct skill practice in 21st century skills which quickly becoming the norm in school curriculums. Games-based inquiry encourages student engagement, collaboration with peers, critical thinking, problem-solving, and a deep understanding of increasingly complex systems. Ultimately, a games-based inquiry approach hypothetically could employ game design as a creative, generative classroom experience.
Keywords: Games-based learning; Metagaming